Radiological aspects of pulmonary sarcoidosis: An integrative review of the literature (Research, Society and Development, 2023)
Introduction: Sarcoidosis is a multisystemic condition of unknown etiology, characterized by the presence of non-caseating granulomas. Its most common symptoms involve the respiratory system, through coughing, shortness of breath and bronchial hyperreactivity, although it can also present with fatigue, night sweats, weight loss and erythema nodosum. The diagnosis of pulmonary sarcoidosis is more sensitive when performed using computed tomography (CT), allowing the detection of adenopathy and subtle parenchymal changes. The prevalence ranges from less than one case to 40 cases per 100,000 people in the general population, mainly affecting adults under 40 years of age, with a peak incidence in the third decade of life. Objective: To describe the typical forms of pulmonary sarcoidosis using CT, highlighting its importance for the diagnosis of the disease studied. Method: This study is a literature review on the radiological aspects of sarcoidosis based on an active search of bibliography in databases such as Scientific Electronic Library Online (SCIELO), Google Scholar and National Library of Medicine (PubMed MEDLINE), with descriptors “Sarcoidosis”, “Computed Tomography” and “Radiology”. Results: The typical findings found on CT in pulmonary sarcoidosis are nodules, ground-glass opacities, parenchymal opacities, reticular opacities, air trapping, fibrosis, and bronchiectasis. Conclusion: Thoracic sarcoidosis is complex and is often confused with other lung diseases. Severe cases have a major impact, increasing morbidity and mortality. High-resolution tomography is more effective and sensitive in diagnosis. Therefore, radiologists are essential to identify sarcoidosis and reduce risks.